The Tower of London - Penguin Books Ltd (London, United Kingdom Penguin Books Ltd, 1996)
For centuries the Tower has kept watch over the City of London and the River Thames. In this book, the history of this former palace, fortress and prison, and the story of the people who have lived within its walls are retold. It includes the royal collections of armour and weapons.
Keywords: Narrative Nonfiction -- Narrative Nonfiction